A New Damage Model of Rock Considering Residual Strength under Seepage Pressure. (13th June 2022) - Zhilei, He
Abstract : Seepage pressure changes the rock structure and stress state, inducing rock mass damage and destruction under hydromechanical coupling. To describe the deformation characteristic and the entire stress–strain process, we suppose that rock consists of damaged part, undamaged part, and voids part. The three parts are intermingled to carry external loads and the undamaged part gradually becomes damaged part in compression. A redefinition of the damage variable and evolution equation is proposed incorporating damage mechanics and statistical damage theory. Considering that axial loads of the damage parts equal to residual strength, a new statistical damage softening constitutive model is developed. The model is validated by using the experimental data. The proposed model can reflect the entire stress–strain law very well, especially softening deformation characteristics after the peak. The research results are helpful in the rock mass engineering safety analysis under seepage pressure.